Proses Pengembangan Daya Kritis Mahasiswa dalam Mata Kuliah Nihonjijou Melalui Pembelajaran Berbasis Proyek - Diner, Lispridona (Universitas Muhammadiyah Yogyakarta, 2020)
Introducing Japanese culture to Japanese language learners is expected to increase their interest in learning Japanese. Getting to know Japanese culture can also come from other lectures such as kaiwa, dokkai, chokai. Learning Japanese culture has been good so far, namely using two-class activities,